The economics of dependence: A theory of relativity - Hans Friederiszick; Steffen Reinhold (European School of Management and Technology (ESMT), 2021)
An increasing number of countries have introduced some form of prohibition of abuses of economic dependence or broadened the scope of their existing legislation. Yet, very little has been written on the economics of economic dependence, that is on economic reasoning, tools or metrics that can be relied upon to identify whether a company is economically dependent on another company. The present paper aims to fill this gap, and argues that bargaining theory and the economics of relative market power can be helpful to characterise economic dependence. We summarise a number of takeaways from this literature, and describe empirical strategies that can be relied upon to try and quantify economic dependence in specific cases.
Keywords: D43; D86; L42; K21; 650; economic dependency; bargaining theory; vertical restraints; law & economics; competition law